2017
DOI: 10.1017/s0017089516000665
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Connectedness of the Branch Locus of Rational Maps

Abstract: Abstract. Milnor proved that the moduli space M d of rational maps of degree d ≥ 2 has a complex orbifold structure of dimension 2(d − 1). Let us denote by S d the singular locus of M d and by B d the branch locus, that is, the equivalence classes of rational maps with non-trivial holomorphic automorphisms. Milnor observed that we may identify M 2 with ‫ރ‬ 2 and, within that identification, that B 2 is a cubic curve; so B 2 is connected and S 2 = ∅. If d ≥ 3, then it is well known that S d = B d . In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The above, in particular, permits to observe that B 2 = ∅ is connected. For d 3, it is known that B d = ∅ is the locus where M d fails to be a topological manifold [14] and, in [11], it was observed that B d is always connected.…”
Section: The Branch Locus Of Moduli Space the Branch Locus Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The above, in particular, permits to observe that B 2 = ∅ is connected. For d 3, it is known that B d = ∅ is the locus where M d fails to be a topological manifold [14] and, in [11], it was observed that B d is always connected.…”
Section: The Branch Locus Of Moduli Space the Branch Locus Of Mmentioning
confidence: 99%
“…In this case, dim C (M d,Z 2 ) = d − 1, in particular, M d,Z 2 = ∅. In [11], we used this observation to obtain the connectedness of B d . Remark 5.…”
Section: Corollary 1 ([14]mentioning
confidence: 99%
“…where the cuspid (−6, 12) corresponds to the class of a rational map φ(z) = 1/z 2 with Aut(φ) D 3 (the dihedral group of order 6); all other points in the cubic correspond to those rational maps with the cyclic group Z 2 as full group of holomorphic automorphisms. In [5] it was observed that B d is always connected.…”
Section: Introductionmentioning
confidence: 99%